THE MODELING OF NON-STATIONARY PROCESS OF THE AIR POLLUTION INDOOR - Belyaeva, V. V. (Science and Transport Progress, 2008)
The mathematical model to simulate the toxic gas dispersion inside an industrial room after accident ejections was developed. The model is based on the K-gradient transport model and equation of potential flow. The model permits to calculate the time of appearance of concentration when the blast can take place. The results of numerical experiment on predicting the air pollution inside an industrial room are presented.